Magnetic thermoresponsive ionic nanogels as novel draw agents in forward osmosis. Issue 20 (6th March 2015) - Zhou, Aijiao; Luo, Huayong; Wang, Qin; Chen, Lin; Zhang, Tian C.; Tao, Tao
<x xml:space="preserve">Abstract</x> Magnetic thermosensitive ionic nanogels were prepared based on strong ionic monomer AMPS and thermosensitive monomer NIPAM via precipitation polymerization in the presence of Fe3O4 nanoparticles and investigated as draw solutes in FO.